Work from Home during Pandemic of Covid-19: Effects on Work Life Balance and Job Satisfaction - Suryani, Irma; Megawati, Megawati; Rahmani, Sari (Universitas Syiah Kuala, 2021)
Objective This study is intended to see the relationship among three variables namely work from home, work life balance, and job satisfaction particularly during COVID-19 pandemic.Design/methodology The research is a descriptive research method. Using online ques-tionnaire, a total of 150 higher education lecturers in Universitas Syiah Kuala, Aceh, Indonesia participated in the survey. The survey was conducted in December 2020. The data was ana-lyzed using SPSS.Results This research revealed that there is a significant relationship between work from home and job satisfaction during COVID-19 outbreak in higher education lecturers, with the intervening variable of Work-Life balance also shows a significant impact toward job satisfac-tion.Research limitations/implications This study has some limitation namely the small amount of data sample and focus only in one sector of sample participants (higher edu-cation lecturers), also this study only exercise three variables, meanwhile it is important to seek both personal and social factors such as person personality, behavior tendency, etc.Novelty/Originality This study covers the impact of COVID-19 pandemic towards job related issues in the university context with participants mainly the lectures.